2021
DOI: 10.1101/2021.05.17.444507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tafazzin regulates the function of lipopolysaccharide activated B lymphocytes in mice

Abstract: B lymphocytes are responsible for humoral immunity and play a key role in the immune response. Optimal mitochondrial function is required to support B cell activity during activation. We examined how deficiency of tafazzin, a cardiolipin remodeling enzyme required for mitochondrial function, alters the metabolic activity of B cells and their response to activation by lipopolysaccharide in mice. B cells were isolated from 3 month old wild type or tafazzin knockdown mice and incubated for up to 72 h with lipopol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…B lymphocytes are essential for adaptive and humoral immunity. We recently reported that Taz deficiency in B cells reduced their metabolic activity and function during activation 43 . However, the role of Taz in regulating MSCs function and the impact of Taz deficiency in MSCs on other cells of the immune system had never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…B lymphocytes are essential for adaptive and humoral immunity. We recently reported that Taz deficiency in B cells reduced their metabolic activity and function during activation 43 . However, the role of Taz in regulating MSCs function and the impact of Taz deficiency in MSCs on other cells of the immune system had never been investigated.…”
Section: Discussionmentioning
confidence: 99%